Fulminant Strokes Secondary to Radiation-induced Small-vessel Arteriopathy. Issue 1 (2nd May 2014) - Kassardjian, Charles D.; Breiner, Ari; del Campo, Martin
<x content-type="archive" xml:space="preserve">Abstract</x> Delayed vasculopathy associated with prior brain irradiation is a known cause of stroke. Radiation is implicated in large-vessel stenosis, cavernous malformations and, rarely, small-vessel disease. There have been no reported cases of fulminant ischaemic and haemorrhagic strokes secondary to radiation vasculopathy. We present the case of a 40-year-old woman with a history of childhood leukaemia and whole-body and cranio-cervical radiation. The patient presented with recurrent acute neurological deficits over a 4-month period resulting from haemorrhagic and ischaemic strokes. Imaging revealed numerous cavernomas and small-vessel acute infarctions. No traditional stroke aetiology was identified. Delayed radiation-induced vasculopathy should be considered in patients with a history of brain irradiation and ischaemic or haemorrhagic strokes, and can present in a fulminant manner with recurrent strokes over a short period of time.